Lipases in ionic liquids system for biodiesel production: A review - Elgharbawy, Amal A.; Alam, Md. Zahangir; Riyad, Fatimah Azizah; Saheed, Olorunnisola K; Moniruzzaman, Mohammed (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Room temperature ionic liquids (RTILs) are molten salts which are liquids at room temperature. Compared with traditional solvents, ionic liquids (ILs) have many advantages such as high chemical and thermal stability, low volatility and non-flammability. According to the literature, ILs have the ability to dissolve many polymers. Moreover, it is feasible to design the physicochemical properties of an IL which extend their scope. As greener solvent, IL-enzyme catalyzed relations have attracted considerable attention. Lipases are one among the important enzymes in both industrial and pharmaceutical sectors that catalyze synthesis, hydrolysis and transesterification of fatty acids esters. It has been shown that lipase is catalytically active in hydrophobic ILs with hexafluorophosphate or bis(trifluoromethanesulfonyl) imide anions while the activity is less in hydrophilic ILs with nitrate or acetate anions. Lipase is used in catalytic transesterification triglycerides with an alcohol (usually methanol or ethanol) for production of biodiesel. Recently, the enzymatic synthesis of biodiesel has been widely described an eco-friendly process, uses moderate conditions and easier product recovery. However, the main drawback of this approach is the lipase inactivation by alcohol due to its hydrophilic nature and leads to limited recycling operations. Due to their wide applications, ILs have been reported as a medium for catalytic conversion of triglycerides to biodiesel. In this review, we will highlight the recent research on employment of ILs-lipase as a system and its efficiency for biodiesel production including the comparisons with other conventional methods.